Performing Cultural Synthesis: Sendratari Kadita as Ethical Pedagogy in Islamic-Javanese Heritage Preservation and Pluralistic Coexistence - Sukmawaty, Fenty; Wahyuni, Yuyun Sri; Tianqi, Fu; Gunawan, Arfa; Yaya, Sobareeyah (Graduate School of UIN Syarif Hidayatullah Jakarta, 2025)
This study explores Sendratari Kadita as a synthesis of Javanese heritage and Islamic spirituality, reimagining Princess Kadita’s story to promote female agency while integrating Islamic ethics and moral education like patience (ṣabr), retreat (ʿuzlah), and self-purification (tazkiyat al-nafs). Through ethnographic fieldwork—participatory performance observation, interviews with Sanggar Sri Manik’s founder, and textual analysis—the research demonstrates how Islamic norms are embedded via green attire (symbolizing purity), sacred accessories, and minimized mysticism. Sendratari Kadita functions as both cultural preservation and moral pedagogy, merging tradition with communal spirituality. It exemplifies Islam’s adaptability in harmonizing local customs without compromising orthodoxy, offering an inclusive model for cultural sustainability in Indonesia’s pluralistic society. The performance’s aesthetic-religious negotiation fosters coexistence amid diversity, positioning it as a replicable framework for heritage-faith integration. By reframing cultural performance as ethical instruction and interfaith dialogue, this study highlights art’s transformative potential in multicultural contexts, balancing identity preservation with progressive spiritual values.